Pembuatan Peta Wilayah Interaktif Di Padukuhan Sambilegi Lor Sebagai Sarana Informasi Geografis - Kiswiranti, Desi; Dzakiya, Nurul; Setiawan, Dewa Gede Eka (Universitas Negeri Gorontalo, 2025)
Interactive regional maps are one solution for visualizing geographic information accurately, practically, and easily accessible to the public. This activity aims to compile an interactive regional map in Padukuhan Sambilegi Lor, Maguwoharjo. Sleman Regency, Yogyakarta, to support development planning, identification of local potential, disaster mitigation, and promotion of local resource-based tourism. Mapmaking is carried out through several stages, namely preparation, field data collection, data processing with GIS software, validation with the community, and publication of the final results. This map is able to identify potential areas, such as rivers and springs, that can be developed as tourist destinations, as well as displaying important data such as area boundaries, evacuation routes, and public facilities. By involving the community at every stage, this map is expected to increase community participation in village management and support information transparency. The results of this activity are not only useful as a geographic documentation tool but also as a catalyst for inclusive, sustainable, and data-based community development.Keywords: Interactive regional map, sustainable development, Sambilegi Lor, Maguwoharjo.